SUPERVISI AKADEMIK IN HOUSE TRAINING UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MENGGUNAKAN MEDIA PEMBELAJARAN - Putra, Wahyudi; Idi Warsah; Adisel; Jumira Warlizasusi (re-JIEM (Research Journal of Islamic Education Management), 2024)
The main problem faced is the low level of utilization of ICT-based learning media by teachers, where only 20% or 2 out of 10 teachers use it in learning, and the use is not yet optimal. This study aims to describe the application of the In House Training (IHT) academic supervision technique in improving teachers’ ability to use learning media based on information and communication technology (ICT) at Ma’had Rabbani IT High School, Central Bengkulu. This study used a Supervisory Action Research design carried out in three cycles. Data were obtained through observation, assessment instruments, and document analysis. The results showed a significant increase in the utilization of ICT-based media. In the pre-cycle, only 20% of teachers used ICT-based media, but after three cycles of academic supervision through IHT, utilization increased to 100%. Teachers’ competence in using ICT-based learning media also experienced a gradual increase, with an average score of 79 in the first cycle, increasing to 90 in the second cycle, and reaching 94 in the third cycle. This study provides a positive impact on the quality of learning in schools.